Peer-to-peer financing in Islamic finance: an analysis of the musharakah model of Islamic fintech for SMEs financing in the state of Qatar - Adam Sa'ad, Auwal (2018)
Peer-to-peer financial services are increasingly becoming significant game changers in the financial sector across the globe. Initially, few structures were developed to help cater to the attention of the Islamic financial industry players involved in peer-to-peer dealings. The new trend of the technological evolution in the banking and financial sector has proved to be the next challenge in this sector. However, the survival of Islamic Fintech will heavily rely on the existing established trust within the sector. The potential collaborations between the established Islamic banks, Fintech players and start-ups will certainly unleash the potentials of today’s technologies in the Islamic finance industry. The paper proposes a Musharakah model using Musharakah Smart Contract in which the investors would be crediting their investments for Musharakah purposes with virtual business owners for specific Shari‘ah compliant businesses and share in the profit based on an agreed dividend under the Musharakah principles. It also highlights the potential structures, cyber risks, and devices to mitigate them by using Musharakah standards and measures within the Shari‘ah principles.